‘We Were a Distribution Cooperative’: A Few Transformations in the Banned Drugs Market in a Neighborhood in the City of Rosario, from Self-Employment to Commercialization on a Large Scale - Eugenia Cozzi (Dilemas: Revista de Estudos de Conflito e Controle Social, 2020)
The paper analyzes some transformations in the market of banned drugs — marijuana and cocaine — that occurred in the last two decades in an urban-popular neighborhood in the city of Rosario, Argentina. Based on the reconstruction, from an ethnographic perspective, of the path followed by young people belonging to three generations, it is intended to account for more general changes. The transformations will be presented and organized in three dimensions: the forms of organization and internal distribution of tasks and the configuration of varied positions and roles; the form of retail sale; and finally, the ways of linking with the police.